Optimization of cutting current in CNC plasma cutting for improved bracket fabrication quality - Ali Sai'in; Venditias Yudha; Luqman Al Huda; Zaenal Abidin; Hartanto Prawibowo (Politeknik Negeri Lhokseumawe, 2026)
CNC plasma cutting is widely used in metal fabrication due to its efficiency and versatility; however, parameter optimization is essential to ensure high-quality results. This study investigates the influence of CNC plasma cutting parameters affect the fabrication quality of Revo motorcycle brackets, which are essential for electric motor vehicle conversion. We conducted experiments on 6 mm thick low-carbon steel plates using a JIAXIN JX-1530 machine. The electric current was varied at 50, 52, 54, and 56 A. For each current level, four specimens were prepared and tested while keeping other parameters constant: a cutting speed of 600 mm/min, a gas pressure of 6 bar, and a torch distance of 1–2 mm. We assessed cut quality based on surface roughness (Ra) at two measurement points, dimensional accuracy relative to CAD design, and hardness variations in the Heat-Affected Zone (HAZ) and base material. The results showed that the best conditions were achieved at 50 A, 6 bar gas pressure, and a torch distance of 2 mm, resulting in an average Ra of 5.39 µm and a dimensional deviation of ±0.3 mm. Although increasing the current above 50 A improved HAZ hardness, it negatively impacted surface roughness and increased the risk of thermal defects. These findings indicate that the identified optimal parameters support the production of high-precision, cost-effective brackets.